2017
DOI: 10.1016/j.bmcl.2017.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and in vitro cytotoxicity studies of novel β -carbolinium bromides

Abstract: A series of novel β-carbolinium bromides has been synthesized from easily accessible β-carbolines and 1-aryl-2-bromoethanones. The newly synthesized compounds were evaluated for their in vitro anticancer activity. Among the synthesized derivatives, compounds 16l, 16o and 16s exhibited potent anticancer activity with IC values of <10μM against tested cancer cell lines. The most potent analogue 16l was broadly active against all the tested cancer cell lines (IC=3.16-7.93μM). In order to test the mechanism of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…All reagents were purchased from commercial suppliers and were dried and purified when necessary. The following intermediates 3a - 3b 29 , 3c - 3e 21 , 3f 30 , 3g 31 , 3h 32 , 4g - 4h 33 were prepared as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…All reagents were purchased from commercial suppliers and were dried and purified when necessary. The following intermediates 3a - 3b 29 , 3c - 3e 21 , 3f 30 , 3g 31 , 3h 32 , 4g - 4h 33 were prepared as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…Anti-proliferation and apoptosis induction were demonstrated as the main cytotoxic effects. For example, harmine and its analogues have the function of anti-proliferation and apoptosis induction in many cancer cell lines, such as human thyroid cancer TPC1 cells, human colorectal carcinoma SW620 cells and human prostate cancer C4-2 cells [ 21 , 22 , 23 ]. Our previous research found that harmine could induce G2/M cell cycle arrest and apoptosis in the Spodoptera litura SL-1 cell line [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…We emphasize that, using these parameters to compare drug efficacy between distinct cell populations (such as cell lines), cells that grow “faster” in culture will be inferred more sensitive than “slower” ones, and therefore these parameters lead to a misinterpretation of the results because of their dependency to the unique growth properties of each cell population. Despite PG partially overcomes this limitation, we provide in the first section of the results a detailed description of the dependency of R , and consequently the IC 50 , to cell proliferation rate because of its frequent usage in current anticancer drug discovery research (as few recent examples (Ben et al, ; Cabrera et al, ; Esposito et al, ; Hamed, Darwish, Herrmann, Abadi, & Engel, ; Indovina et al, ; Koul et al, ; Mathema, Chaijaroenkul, Karbwang, & Na‐Bangchang, ; Menderes et al, ; Mukunthan, Satyan, & Patel, ; Muñoz, Rosso, & Coveñas, ; Potenza et al, ; Ravi, Ramesh, & Pattabhi, ; Rimoldi et al, ; Said, Brouard, Quintana, & Estévez, ; Venkataramana Reddy et al, ; Wehbe et al, ; Zamora et al, ; Zhu et al, )). Subsequently, in the second section of the results, we show that PG is also dependent on the growth properties of the cells, because of their exponential and not linear proliferation in culture.…”
Section: Introductionmentioning
confidence: 99%